The posterior insula as an independent pain center: Two cases of isolated facial pain-type epilepsy revealed by stereo-electroencephalography - Jun Zhuang; Lingxia Fei; Hua Li; Qiang Guo (Epilepsy & Behavior Reports, 2025)
Within the spectrum of epileptic syndromes, insular epilepsy presents significant diagnostic complexity, making it a challenging entity in clinical practice. The insula, located deep within the lateral fissure, exhibits highly heterogeneous and non-specific ictal manifestations, frequently leading to misdiagnosis as other medical conditions. This study presents two cases of insular epilepsy with isolated facial pain as the sole clinical manifestation. Using stereotactic electroencephalography (SEEG), we precisely localized the seizure onset zone (SOZ) to the posterior insular cortex in both patients. Based on SEEG data, we conducted comprehensive analysis of the ictal epileptogenic networks and performed relevant literature review. Our findings aim to enhance clinicians’ recognition of atypical presentations of insular epilepsy and provide novel clinical perspectives and diagnostic approaches for the differential diagnosis of refractory facial pain.